Ethnoscience-Based Project Learning Rooted in Sundanese Indigenous Ecological Knowledge: Effects on Environmental Awareness, Environmental Responsibility, Scientific Literacy, and Sustainability Awareness among Junior High School Students - Muhammad Rizky Aulia; Dhika Surya; Jumadil Saputra (International Journal of Ethno-Sciences and Education Research, 2026)
Science instruction in many Indonesian junior high schools remains largely decontextualized from students' own cultural surroundings, a condition that has been associated with persistently low environmental literacy and a weak sense of ecological responsibility among adolescents. Ethnoscience-based learning offers a way to reconnect formal science with indigenous ecological knowledge, yet most existing studies have used it mainly to raise scientific literacy or as descriptive documentation of local wisdom, rather than as a live, field-based project learning experience whose effect is tested simultaneously across environmental and scientific outcomes. This study proposes and evaluates an Ethnoscience-Based Project Learning (EBPL) design that embeds the indigenous ecological knowledge of the Sundanese customary community of Kampung Kuta, Ciamis Regency, West Java — including its sacred-forest conservation system (Leuweung Gede), communal water-source governance, palm-sugar agroforestry, and home-garden medicinal-plant practices — into a science unit on environmental pollution and ecosystem sustainability. A quasi-experimental nonequivalent control-group design was used, involving eighth-grade students assigned to an experimental group (EBPL) and a control group (conventional project-based learning without explicit ethnoscience content). Four constructs were measured before and after the six-week intervention: environmental awareness, environmental responsibility, scientific literacy, and sustainability awareness. [Results to be completed after the study is conducted]. The study is expected to show that grounding project-based learning in a specific, living indigenous knowledge system produces larger gains than generic project-based learning, and it argues that ethnoscience-based project learning can simultaneously serve science-literacy goals and the preservation of endangered local ecological wisdom. Implications for science curriculum design under Indonesia's Merdeka Curriculum, particularly the Projek Penguatan Profil Pelajar Pancasila (P5), are discussed.